Plundered Promise: Capitalism, Politics, and the Fate of the Federal Lands - Behan Richard W (Island Press, 2001)
What has been done to our public lands? Irreplaceable forests harvested for lumber. Vast expanses of rangeland leased at rates far below market value. Mineral resources extracted with little or no royalties paid. These and other actions have brought unparalleled benefit to private interests-and massive costs to society at large. They are but the most visible signs of the fundamental flaws in the current system of federal lands management. In Plundered Promise, leading resource management scholar Richard W. Behan presents an engrossing history and analysis of public lands management in the United States, as he describes how we arrived at the current situation and examines what we can do to rectify it.